Climate change in Colorado [flyer] - Colorado Climate Center, author (Colorado State University. Libraries, 2024)
Flyer advertising the third edition of the Climate Change in Colorado Report which describes recent trends and future projections of Colorado's climate and hydrology.
Keywords: Colorado -- Climate -- Observations; Climatic changes -- Colorado; Meteorology -- Colorado -- Observations